Pengembangan Model Bisnis Layanan Mobile Banking PT. Bank Nagari menggunakan Business Model Canvas - Maharani Adilla; Hafiz Rahman; Ma’ruf (Jurnal Informatika Ekonomi Bisnis, 2023)
Digital transformation has changed the pattern of transactions in society, thus encouraging banks to make digital-based services part of their business strategy. This encourages increased competition in the financial services industry. For that, PT. Bank Nagari needs to identify and develop a business model so that Nagari Mobile Banking services can become a competitive advantage. Where, a good understanding of the business environment will enable companies to evaluate or even develop potential business models going forward. The Business Model Canvas is a business model mapping method that can provide an overview of how a company is able to provide value (value proposition) for its customers. This business model framework consists of 9 (nine) key elements, namely Customer Segments, Value Propositions, Channels, Customer Relationships, Revenue Streams, Key Resources, Key Activities, Key Partnerships, and Cost Structure. The results showed that the Nagari Mobile Banking service needed to develop the Value Proposition, Customer Relationship, Customer Segment, Channel, Key Activities, Key Partners, and Key Resources blocks, while the Cost Structure and Revenue Streams blocks did not experience development.